HISTORICAL ANALYSIS OF THE ART OF EMBROIDERY IN THE UZBEK NATIONAL CRAFT - Mamarajabov, Gayrat Abdulkhakimovich; Izzatullaev, Fazliddin Jovlievich (Current Research Journal of History, 2021)
The art of embroidery, embodied in the world famous masters of the Uzbek people and the national fabrics they create, with its brilliance, variety of colors, Islamic conditions has found its place in the world national art. Although our national embroidery has evolved over the centuries and is distinguished by beauty, diversity and regional differences, in turn, they complement each other. The word kashta comes from the Persian-Tajik language and means "kashida", which means to pull, sew. Embroidery is an important branch of the applied arts of the Surkhandarya oasis. Among the embroidery items of the population of the oasis are suzana, zardevor, borposh, sandalposh, jainamaz, lolabolish, belars (belt), kettle, bag for salt, bag for spoons, glass bag, brick, towels designed to cover beds.